Kartagener syndrome: A diagnostic challenge in advanced age (Research, Society and Development, 2026)
Kartagener Syndrome (KS) is a rare, autosomal recessive form of Primary Ciliary Dyskinesia (PCD), characterized by the classic triad of bronchiectasis, chronic rhinosinusitis, and situs inversus totalis. This study aims to report the case of a 67-year-old female patient with a history consistent with altered ciliary motility, including recurrent respiratory infections since childhood, chronic headache, hearing loss, and obstetric history suggestive of ciliary dysfunction. This is a case report based on clinical evaluation, medical record review, and analysis of complementary exams. During hospital admission for respiratory failure and chest pain, situs inversus totalis, bronchiectasis in the lower lobes, and chronic sinusitis were identified. The investigation confirmed the diagnosis of KS, with a sputum culture positive for Pseudomonas aeruginosa. Culture-guided antibiotic treatment was instituted, along with ventilatory support. This case illustrates the prolonged clinical course and multisystemic manifestations of Kartagener syndrome (KS), reinforcing the importance of early diagnostic suspicion, especially in patients with recurrent respiratory infections and suggestive radiological findings. Timely recognition allows for appropriate therapeutic intervention and prevention of complications.